CT study of products from non-metallic composites reinforced by carbon fibers - Levenets, V.V.; Gurin, I.V.; Ovchinnikova, M.A.; Gurina, Ye.V. (Вопросы атомной науки и техники, 2022)
Computerized tomography is used to study products from non-metallic composites reinforced by carbon fibers. It is demonstrated that samples do not rotate during the analysis process and can have diameter not exceeding the gantry hole (75 cm) of the unit. The weight of samples can be up to 200 kg, and the length during one-time testing does not exceed 150 cm. The results of spatial calibration of the technology are shown using a set of copper wires with diameters from 0.56 to 0.05 mm. The paper presents the results of defects detecting in products in the form of gas pores and metal inclusions.